2020
DOI: 10.1051/e3sconf/202017604002
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon sequestration according to two Geoset long-term field experiments in the Moscow region

Abstract: The feasibility of implementing the "4 ppm" initiative, which assumes an annual increase in organic carbon stocks of agricultural soils in the layer 0-40 cm, was estimated with the dynamic carbon model RothC in two long-term DAOS experiments in the Moscow region, conducted in neighbouring fields for 74 and 76 years. Treatments included absolute control, application of organic, mineral, organic and mineral fertilizers at increasing rates. One of the experiments showed the growth of C stocks 12‰ in the layer 0-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The model was adjusted previously using measured SOC concentrations during the experiment. The model found satisfactory convergence between the experimental and calculated data for all the studied treatments [14]. Figure 1 shows the dynamics of carbon stocks in the arable soil horizon calculated for two climate scenarios.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…The model was adjusted previously using measured SOC concentrations during the experiment. The model found satisfactory convergence between the experimental and calculated data for all the studied treatments [14]. Figure 1 shows the dynamics of carbon stocks in the arable soil horizon calculated for two climate scenarios.…”
Section: Methodsmentioning
confidence: 66%
“…In our previous research, we modelled and verified the dynamics of SOC in DAOS 3 and DAOS 4 experiments for the period 1935-2011 [14]. In the present study, the forecast of the dynamics of organic carbon stocks under the future climate was made for two climate scenarios: RCP4.5 and RCP8.5 from four Representative Concentration Pathways scenarios used in the IPCC fifth assessment report (AR5).…”
Section: Methodsmentioning
confidence: 85%
“…When modelling the dynamics of C in a long-term experiment in the Moscow region on Retisol, we showed that while it is challenging to ensure yield growth for the RCP4.5 scenario and especially RCP8.5, the condition determining the possibility of additional sequestration of C is a decrease in the critical level of annual C input to the soil [11,22]. At the same time, the expected growth is provided only in the period 2020-2040.…”
Section: Discussionmentioning
confidence: 99%
“…We already tested the results of field experiments of the "Geographical experimental network for the use of fertilizers" for practical testing of the agrotechnology's suitability for reaching the goals of the "4 per 1000" initiative [9][10][11]. In this paper, we assess the potential of carbon sequestration by arable sandy Podzols, which are believed to have a high potential for C sequestration [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we had a unique situation with two fields with the same soil and almost identical fertilizer inputs but differing in crop rotations and land use on the starting date of the experiment. The SOC dynamics modeling results for the past were presented in our previous publication [9]. Modeling showed that fertilization and crop rotation modification could provide a steady increase in the C input and soil C accumulation in the 0-20-cm layer.…”
Section: Introductionmentioning
confidence: 99%